Dinamika Ekonomi Politik dalam Regulasi BBM: Studi Kasus Pengoplosan Pertamax di Indonesia - Aulia, Aisyah; M, Melati; N, Nurilawati; Candra, Mellyana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The regulation of fuel oil (BBM) in Indonesia is at the intersection of economic and political interests, where the government as the main regulator must balance various external factors such as pressure from energy companies, political dynamics, and public response. This policy complexity often creates loopholes that are exploited by certain parties, such as in the case of Pertamax bootlegging which reflects regulatory imperfections as well as competing interests between the government, energy companies, and the public. This study aims to analyze how fuel regulations in Indonesia are formed in the context of political economy and their impact on illegal practices such as fuel copying. Using a qualitative approach based on a literature study, this research examines the policies that have been implemented, the challenges faced, and the imbalances in their implementation. The results show that fuel regulations often experience instability due to political intervention and complex economic dynamics, where policy vagueness, weak supervision, and the interests of various parties cause regulations to not always be effective in suppressing illegal practices. Therefore, more transparent, consistent policies and strict monitoring mechanisms are needed so that fuel regulations can run effectively and fairly for all stakeholders.